ASSESSMENT OF INTEGRATED WATER RESOURCES MANAGEMENT PRACTICE IN YATTA CANAL, MACHAKOS DISTRICT, KENYA - Simitu, Lawrence N.; Odira, Patts M. A. (Tanzania Journal of Engineering and Technology, 2018)
Yatta Canal is situated in Yatta division, Machakos district about 100 km from Nairobi along Thika- Garissa road. It is about 60 Km long and supplies water for domestic, livestock and irrigation use. Over the years, the water supply has been unreliable especially during dry season leading to conflicts between upstream and downstream consumers. Sometimes the Government has been forced to intervene to restore order. The study aimed at assessing the use of Yatta canal, based on the principles of Integrated Water Resources Management (IWRM) which stipulates efficient use of water and involvement of all stakeholders in decision making for sustainability. Based on this concept, it was established that the current water demand outstrips supply and that there is inefficient water use especially for irrigation. Water allocation process favours landowners, and stakeholders are not fully involved in planning, management and development. Further, women ' s participation in decision-making is minimal. There is no environmental voice during water allocation and thus the reserve/ base flow in the canal has not been maintained. This means that IWRM concept has not been practiced and this has resulted to conflict among various water users. As Yatta canal gets water from Thika river, there is need to establish Thika river basin water users association where stakeholders can influence decisions on water allocation and management. This will create a forum to discuss efficient water use at all levels and promote internal policing to ensure fair allocation, thus minimizing conflicts and promoting the IWRM concept.